Cálculo de la pérdida de transmisión acústica y de contrapresión en silenciadores, mediante el método de los elementos finitos (2017)
This article presents the simulation of Transmission Loss and the Back Pressure of mufflers by means of Finite Element Method. These two variables are inversely proportional, reason why its balance is searched in muffler’s design process to achieve a high Transmission Loss and a low Back Pressure. The calculations were obtained using the ANSYS APDL and Siemens NX Flow software. The simulations of the results obtained were compared and validated with the experimental results and the sub-structured modal method presented by other authors.